Determinants of Anemia in Pregnant Women in Semarang City in 2023 - Rahmawati, Siska; Azam, Mahalul; Rahayu, RR. Sri Ratna (Universitas Negeri Semarang, 2024)
Anemia during pregnancy can lead to serious complications, such as bleeding and premature birth. The prevalence of anemia in Semarang in 2022 reached 15.4%, exceeding the WHO target. This study aims to analyze factors influencing the occurrence of anemia among pregnant women in Semarang in 2023. The study was conducted at five public health centers in Semarang with 183 pregnant women, consisting of 61 with anemia and 122 without anemia. Data were collected from January to July 2024, with analysis using Chi-Square and logistic regression tests. Significant factors associated with anemia included age (p=0.006), employment status (p=0.005), gravidity (p=0.047), ANC history (p=0.036), compliance with iron supplementation (p=0.003), tea/coffee consumption habits (p=0.024), iron intake from food (p=0.033), nutritional status (KEK) (p=0.041), and knowledge about anemia (p=0.009). Multivariate analysis showed that age (OR=3.09), employment status (OR=0.395), and KEK status (OR=2.99) were higher risks for anemia. Age, employment status, and nutritional status (KEK) are significant factors affecting anemia in pregnant women in Semarang, highlighting the importance of nutritional interventions and health education for pregnant women.